Influence Discipline And Competence Of Teachers To Work A Teacher In High School Subdistrict Pedamaran - Malia, Malia; Lian, Bukman; Eddy , Syaiful (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
Requiring teachers to have good working performance .A teacher is a produced by a teacher in conducting its function as an education and teachers to follow in the classroom according to criteria which has been so that it may become teachers professional .Professional teachers itself is teacher are also , competent , discipline , and teachers is intended to bring about learning achievements and able to influence on the students will produce better students achievement .The hypothesis advanced by this , work is the discipline on the performance of a high school teacher in kecamatan pedamaran , is the competence of teachers on the performance of a high school teacher in kecamatan pedamaran , is the discipline of work and competence of teachers ame together on the performance of a high school teacher in kecamatan pedamaran.